Comparative genomic analysis of Vibrio Cholerae and its colonization factors / Cindy Teh Shuan Ju. - Teh, Cindy Shuan Ju (2011)
Vibrio cholerae, the causative agent of cholera, is endemic in Malaysia and is spread through the ingestion of contaminated food or water. The aims of this study were to develop a multiple PCR assay for differentiation of V. cholerae from other Vibrio species; to compare the efficiency of PCR assay with conventional biochemical tests and API 20E.; to characterize the strains based on their biotypes, serogroups, and virulotype by using a multiplex PCR assay; to determine the genetic relatedness of strains by using genotyping methods such as RAPD-PCR, ERIC-PCR, REP-PCR, MLVA, PFGE, MLST and MVLST; to study the virulence factors which cause colonization in different serogroups of V. cholerae; and the influence of host environment for colonization. Four pairs of primers were designed for differential detection of sister groups of Vibrio species Strains tested were differentiated into V. cholerae (493/338 bp), V. parahaemolyticus (493/409 bp), V. vulnificus (493/656 bp), Vibrio species (493 bp), and non-Vibrio (no amplification) based on pntA and gyrB genes. This multiplex PCR assay was more sensitivie and specific than API 20E identification assay. Another multiplex PCR assay based on ompW, hlyA, orf complex, toxR, ctxA, tcpI for V. cholerae biotyping, serogrouping and virulotyping was developed and tested on 43 V. cholerae strains. A total of 22 El Tor O1 and one O139 V. cholerae that harboured all virulence genes were identified. One El Tor O1 V. cholerae presented identical virulotype to 17 other non-O1/non-O139 V. cholerae, while the tcpI gene was detected in two non-O1/non-O139 V. cholerae. The 43 strains were also subtyped into 38, 40, 35, 30, 35, 38, 29 and 27 profiles by RAPD-PCR, ERIC-PCR, REPPCR, VCR-PCR, PFGE, MLVA, MLST and MVLST, respectively with discriminatory power ranging from 0.910 to 0.996. Overall, genetic diversity of non-O1/non-O139 V. cholerae strains was high while some of the O1 strains were indistinguishable. However, iv the unrelated strains which shared the same profiles were distinguished based on the combined analyses of the eight genotyping methods. However, each method possesses its own limitations. MLST and MVLST gave precise description of point mutation but were expensive. Overall, MLVA developed in this study remains the most suitable genotyping methods based on discriminatory ability, ease of operation, cost, timeline and data management. However, a combination of several genotyping methods may overcome the inefficiency of each single method and therefore able to distinguish unrelated strains. Finally, clinical and environmental O1 strains could colonize the mouse intestines but prolonged colonization was only observed with environmental strains which showed upregulated expression of rtxA and hlyA genes. The tcpI+ non-O1/non-O139 V. cholerae strain was a more efficient colonizer while the non-toxigenic O1 V. cholerae could colonize the mouse intestine once the virulence genes were favourably enriched and ‘turnon’ in the host environment. In conclusion, this study provided alternative approaches for rapid differentiation of V. cholerae from other pathogenic Vibrio species, as well as to biotype, serogroup and virulotype the V. cholerae strains. Regardless of serogroups, year, source and location of isolation, all the unrelated strains were distinguishable and therefore suggests a high diversity of V. cholerae population in Malaysia. Different traits of strains posses different colonization ability and tcpI gene might be the key regulator for colonization in non-O1/non-O139 V. cholerae. However, colonization in non-toxigenic O1 V. cholerae might be facilitated once the virulence genes were ‘enriched’ in the host environment.